The Development of a Clinical Supervision Model for Isolation Precaution of Antimicrobial Resistance at Neurological Surgery Department, Sunpasitthiprasong Hospital - Boonsong, Somsamai; Noimuenwai, Premruetai; Prasertsri, Nusara (Journal of The Royal Thai Army Nurses, 2021)
The purposes of this research and development study were: 1) to develop a clinical supervision model for isolation precaution of antimicrobial resistance at neurological surgery department, Sunpasitthiprasong hospital, and 2) to evaluate the developed clinical supervision model on head nurses knowledge, nursing competency and the registered nurses’ perceptions. The samples were composed of 2 groups. The discussion group in the developmental stage included 3 head nurses and 6 registered nurses. The second group who evaluated the developed clinical supervision model included 6 head nurses and randomized samples of 52 registered nurses from the Neurological Surgery Department. The experimental tools were composed of: 1) focus group question and the developed clinical supervision model. 2) The data collection tools composed the clinical supervision knowledge test, competency evaluation form, and the questionnaire for perception of clinical supervision. All research tools were validated for content by 5 experts. The content validity indexes of these tools were 0.88, 1.00 and 1.00. The reliability (KR-20) of the clinical supervision knowledge test was 0.75. The Cronbach’s alpha reliability coefficient of the competency evaluation form and the questionnaire for perception of clinical supervision results were 0.94 and 0.83. Data was analyzed by descriptive statistics, content analysis, and Wilcoxon matched-pairs signed-ranks test. The results are as follows. 1) The developed clinical supervision model based on the three functions Proctor’s model. 2) knowledge of head nurses significantly higher than before receiving. (p< .05). Competency of registered nurses significantly higher than before receiving. (p< .001), and perceptions of supervision at the good level.